Rebel mechanics : all is fair in love and revolution - Swendson, Shanna (Square Fish, 2016)
In 1888 New York City, sixteen-year-old governess Verity Newton agrees to become a spy, whatever the risk, after learning that the man for whom she has feelings sympathizes with rebels developing non-magical sources of power, via steam engines, in hopes of gaining freedom from British rule.